1996
DOI: 10.1046/j.1365-2443.1996.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

D‐type cyclin expression is decreased and p21 and p27 CDK inhibitor expression is increased when tsBN462 CCG1/TAFII250 mutant cells arrest in G1 at the restrictive temperature

Abstract: Background: The tsBN462 temperature-sensitive mutant hamster cell line exhibits cell cycle arrest and apoptosis at the restrictive temperature of 39.5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 53 publications
(76 reference statements)
4
30
0
1
Order By: Relevance
“…At the restrictive temperature of 39.58C, tsBN462 cells arrest in G1 (Sekiguchi et al, 1987) and subsequently undergo apoptosis (Sekiguchi et al, 1995). Previously, we showed that D-type cyclin expression is decreased and p21 and p27 expression is increased in tsBN462 cells at 39.58C (Sekiguchi et al, 1996). This phenotype is similar of that of UV-irradiated cells arrested in G1, suggesting that CCG1/TAF II 250 is a key player in coordinating G1 phase cell cycle arrest.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…At the restrictive temperature of 39.58C, tsBN462 cells arrest in G1 (Sekiguchi et al, 1987) and subsequently undergo apoptosis (Sekiguchi et al, 1995). Previously, we showed that D-type cyclin expression is decreased and p21 and p27 expression is increased in tsBN462 cells at 39.58C (Sekiguchi et al, 1996). This phenotype is similar of that of UV-irradiated cells arrested in G1, suggesting that CCG1/TAF II 250 is a key player in coordinating G1 phase cell cycle arrest.…”
Section: Introductionmentioning
confidence: 64%
“…Rescue of tsBN462 G1 cell cycle arrest by D-type cyclins Previously, we showed that D-type cyclin (cyclin D1 and D3) expression was decreased and that p21 cip1/waf1/sdi1 and p27 kip1 expression was increased in tsBN462 cells at the nonpermissive temperature of 39.58C; in combination these events would be expected to preclude Rb phosphorylation and thereby cause cell cycle arrest (Sekiguchi et al, 1996). In the same report, we observed that the underphosphorylated form of Rb was increased in tsBN462 cells at 39.58C.…”
Section: Resultsmentioning
confidence: 98%
“…When p21 expression was induced in growing Tet-p21-1 and Tet-p21-3 cells, p21-associated histone H1 kinase activity increased about fourfold reaching a maximum between 10 and 15 h and declining thereafter (Figure 3a,b). In control cells, which contain the tTA vector, a constant low level of histone H1 kinase activity was detected in anti-p21 immunoprecipitates, which is presumably due to cyclin-Cdk's associated with endogenous hamster p21, which is recognized by the anti-p21 antibody used in this assay (Sekiguchi et al, 1996), although the a nity for hamster p21 may be weaker than for human p21. Under the conditions where p21 increased, the levels of Cdc2 and Cdk2 did not change signi®cantly (Figure 3c).…”
Section: Histone H1 Kinase Activity Associated With P21mentioning
confidence: 94%
“…In CD20-positive cells, a signi®cant decrease in the percentage of cells in S phase and a concomitant increase in those in G1 phase was observed in the absence of Tet (induced condition) but not in the presence of Tet (uninduced condition) or in control vector expressing cells (Figure 1a ± d,i ± k). Cell cycle arrest caused by g-irradiation or TGF-b, or in tsBN462 cells at the nonpermissive temperature may result from an inability to release the E2F transcription factor from Rb and Rb family proteins, due to p21-mediated inhibition of cyclin D-Cdk and cyclin E-Cdk complex kinase activity and/or a decrease in cyclin D-Cdk levels DeGregori et al, 1995;Sekiguchi et al, 1996). E2F-1 can overcome TGF-b-induced cell cycle arrest (Schwarz et al, 1995) and temperaturedependent cell cycle arrest in tsBN462 cells (TS and TH, unpublished results).…”
Section: Establishment Of Bhk21 Cell Lines Inducibly Expressing P21mentioning
confidence: 99%
“…While the cell cycle regulatory functions of TAF II s are not fully understood, progress has been made. Molecular and genetic analysis revealed that yTAF145, hTAF250 and mTAF30 are required for the transcription of G 1 /S cyclin genes, and inactivation of conditional alleles in these genes in their respective organisms resulted in cell cycle arrest in G 1 (Martin et al, 1999;Walker et al, 1997;Wang and Tijan, 1994;Sekiguchi et al, 1996;SuzukiYagawa et al, 1997). These important observations have provided an attractive model of how these TAF II s control cell cycle progression, by controlling the transcription of cyclins and other cell cycle regulatory genes.…”
Section: Introductionmentioning
confidence: 99%